Condições de trabalho e transtornos mentais comuns em professores da rede básica municipal de encino de Bauru-SP - Carraro, Maria Marília [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Cross-sectional survey, undertaken after approval by the Committee of Ethics in Research of the Faculty of Medicine Botucatu - UNESP, on first grade school teachers employed by the local education authority of the city of Bauru, Sao Paulo state. Out of a total of 396 active teachers from sixteen local authority schools, 374 participated in the study. The data was collected from August to December 2013 using an anonymous self-reporting questionnaire. Consisting of 72 items, the survey covered socio-demographic and occupational factors, as well as the occurrence of common mental disorders (CMD), and the degree of job satisfaction. Work related psychological demands were also evaluated, as well as the degree of control by teachers in relation to their own work and the social support received in work, utilising the Job Content Questionnaire (JCQ), according to Kasarek's model. The occurrence of common mental disorders, CMD, was investigated trough the Self-Reporting Questionnaire (SRQ-20). The sociodemographic and occupational factors comprised the exposure variables, and the common mental disorders the conclusion variable. The results were analysed through the use of multiple logistic regression. It has been observed a frequency of 36% of CMD. In the adjustment of the logistical regression of multiple conditions model, the following characteristics remained associated with the occurrence of common mental disorders, to be aged between 25 and 39, have dependents, not to believe to be able to remain in work without too many difficulties and for many years with the same work conditions, as well as to be part in and highly stressing active work situations. The high prevalence of CMD amongst teachers suggests the need for public intervention by the local authority with the aim of improving the work conditions and mental health of the teachers in municipal schools in Bauru - São Paulo state

Estudo de corte transversal realizado - após aprovação do Comitê de Ética em Pesquisa da FMB - UNESP, entre a população de professores do ensino fundamental da Secretaria Municipal de Educação de Bauru - SP. Dos 396 professores em exercício de atividades de ensino nas dezesseis escolas municipais de ensino fundamental, 374 participaram do estudo. A coleta de informações, efetuada de agosto a dezembro de 2013, foi realizada por meio de questionário auto-aplicado e não identificado. Composto por 72 itens, o questionário abordou aspectos sócio-demográficos e do trabalho, bem como a ocorrência de transtornos mentais comuns. Dentre os aspectos do trabalho investigou-se o grau de satisfação no trabalho. Foram avaliadas também as demandas psicológicas no trabalho, o grau de controle do trabalhador sobre seu trabalho e o grau de suporte social no trabalho, tendo-se utilizado para tanto o Job Content Questionnaire, JCQ, segundo o modelo de Karasek. A ocorrência de transtornos mentais comuns, TMC, foi investigada por meio do Self Reporting Questionnaire (SRQ-20). Os aspectos sócio-demográficos e do trabalho constituíram as variáveis de exposição e os transtornos mentais comuns, a variável de desfecho. Os resultados obtidos foram analisados por meio de regressão logística múltipla. Observou-se prevalência de 36% de TMC. No ajuste do modelo de regressão logística condicional múltipla permaneceram associados à ocorrência de TMC ter idade de 25 a 39 anos, possuir dependentes, não acreditar ser possível permanecer no emprego sem muitas dificuldades e por muitos anos mantidas as mesmas condições de trabalho, bem como enquadrar-se nas situações de trabalho ativo e de alto desgaste. A elevada prevalência de TMC entre os professores indica necessidade de intervenção do poder público municipal visando melhorar as condições de trabalho e de saúde mental dos professores do ensino fundamental das escolas...
Work conditions and common mental disorders among school teachers from or the city of Bauru, São Paulo state
Keywords: Professores; Saude e trabalho; Doenças mentais; Epidemiologia; Saúde pública; Public health; Teachers; Bauru (SP)